A Turning World: a Multidisciplinary Approach to the Spinning Top and other Toys and Games - Lambrugo, Claudia (Milano University Press, 2023)
This volume presents the results of a research project carried out by a team at the University of Milan. Since meeting almost 'for fun' in 2009, this team has grown over the years, and has now a place in international research on the value of playful activities and artifacts. More precisely, this publication is associated with the LALLACT project (Lexicon of Ancient Ludonims, Ludic Activities, and Cultural Tradition), which is dedicated to creating a digital Lexicon of games, starting with the spinning top and blind man's buff. The collected essays represent the outcome of a fruitful interdisciplinary discussion on these two games. More specifically, the miscellaneous volume proposed here is linked to the LALLACT project - Lexicon of Ancient Ludonims project. Ludic Activities and Cultural Tradition, whose ambitious goal is the creation of a prototype of a digital Lexicon of the game, starting from two 'pilot' voices, respectively the game of the spinning top and blind man's buff. The collected essays constitute the outcome, precious and at times unexpected, of a fruitful multidisciplinary discussion on the topics indicated.